Enhancing Shiga toxin detection using surface plasmon resonance a study of antibody immobilization strategies - Zahra Karbalaee; Ali Hossein Rezayan; Ramezan Ali Taheri; Seyed Ali Mirhosseini; Mohammad Barshan-Tashnizi (Scientific Reports)
Abstract This study demonstrates enhanced detection of Shiga toxin (Stx), a key virulence factor in Shigella dysenteriae-induced bloody diarrhea, through optimized surface plasmon resonance (SPR) biosensor design. We present a comparative evaluation of antibody immobilization strategies, revealing significant advantages of protein G-mediated oriented immobilization over conventional covalent attachment. The covalent (non-oriented) approach using 11-mercaptoundecanoic acid-modified chip showed moderate performance (KD = 37 nM, LOD = 28 ng/mL). In contrast, protein G-assisted orientation dramatically improved detection capabilities, achieving a 2.9-fold lower detection limit (9.8 ng/mL) and 2.3-fold higher binding affinity (KD = 16 nM). Control measurements with free antibody-antigen interactions established a baseline affinity (KD = 10 nM), demonstrating that the oriented method preserves 63% of native binding efficiency versus only 27% in the covalent approach. Mechanistic studies attribute these improvements to protein G’s ability to maintain optimal antibody orientation, thereby: (1) maximizing paratope accessibility, (2) minimizing steric interference, and (3) preserving binding site functionality. The 57% reduction in KD relative to covalent immobilization confirms the method’s efficacy in maintaining antibody performance post-immobilization. These findings establish protein G-mediated orientation as the superior strategy for SPR-based Stx detection, offering substantial improvements in sensitivity and reliability for clinical diagnostics and food safety applications. The approach demonstrates particular promise for rapid, label-free detection of bacterial toxins in resource-limited settings.